2000
DOI: 10.1016/s0735-1097(00)00872-x
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of coronary events with electron beam computed tomography

Abstract: In asymptomatic adults, EBCT of the coronary arteries predicts coronary death and nonfatal MI and the need for revascularization procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
383
0
18

Year Published

2001
2001
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 704 publications
(409 citation statements)
references
References 42 publications
5
383
0
18
Order By: Relevance
“…CAC is also associated with an increased risk of future cardiovascular disease (CVD) in middle-aged populations (1)(2)(3)(4).…”
Section: Study Populationmentioning
confidence: 99%
“…CAC is also associated with an increased risk of future cardiovascular disease (CVD) in middle-aged populations (1)(2)(3)(4).…”
Section: Study Populationmentioning
confidence: 99%
“…Therefore, it is necessary that other tests be used for a better stratification of the risks for coronary events. Data from the literature have shown that the presence of coronary artery calcification is associated with a greater risk for coronary events [11][12][13][14] , and its absence is associated with an almost-zero risk for coronary events in studies of 3-to-5 year follow-up 25 . Coronary artery calcium scores have their major usefulness in stratifying the risk for clinical events.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrafast computed tomography is a noninvasive and very sensitive method to detect calcification in coronary arteries 7 . Evidence exists that the presence of coronary artery calcification on ultrafast computed tomography may be a risk marker of clinical events in coronary artery disease, independent of the risk factors for atherosclerosis [11][12][13][14] . Up to now, coronary artery calcium scores in the Brazilian population have not been reported.…”
Section: Distribution Of Coronary Artery Calcium Scores Determined Bymentioning
confidence: 99%
“…These include exercise electrocardiogram testing (626,627,655), ambulatory electrocardiogram monitoring (656,657), measurement of left ventricular ejection fraction (658,659), magnetic resonance imaging (660), exercise or dipyridamole single-photon emission computed tomography (SPECT) (658,661), positron emission tomography (PET) (662), electron beam computed tomography (663)(664)(665)(666)(667)(668) and thallium/sestamibi scintigraphy (with exercise or dipyridamole) (669-674) echocardiography (with exercise or dobutamine) (675,676). Few studies have assessed exercise electrocardiogram testing in patients with ESRD.…”
Section: Cardiovascular Diseasementioning
confidence: 99%
“…Recently, results of electron beam computed tomography have been shown to correlate with both angiographic coronary artery disease and IHD events (663)(664)(665)(666)(667)(668). However, a study of 1196 high-risk patients found no difference between electron beam computed tomography and traditional risk-factor assessment in predicting coronary events (681).…”
Section: Cardiovascular Diseasementioning
confidence: 99%